THE MAPPING OF RENEWAL OF ‘USUL FIQH ’ THOUGHTS IN INDONESIA - Nispul Khoiri (State Islamic University of North Sumatra Indonesia, 2017)
Abstract, The substance of this paper is the mapping of thoughts of the renewal of ‘Usul Fiqh’ that has popular or being occurred in Indonesia, by expressing the proposed idea of the method of legal istinbat based on detailed arguments and not in favor of the dominance of a particular madzhab. The urgency in the academic context becomes an interesting study to be criticized and developed by activists who are concerned on Islamic law in Indonesia. In the context of law need, the mapping became the initial data to encourage the building of renewal ideas. There are two renewed mindsets: Firstly, institutional reform (NU-Muhamamdiyah, MUI, and others). Secondly, reforms are partial among Indonesian Muslim scholars. The thoughts of the proposed Jurisprudence were categorized into three forms: Contextualization of the school, reconstruction of interpretation and vernacularisation of ‘Ushul Fiqh’ in Indonesia based on local Indonesian culture.